1994
DOI: 10.1159/000126697
|View full text |Cite
|
Sign up to set email alerts
|

Response of Calcitonin-Gene-Related Peptide-Like Immunoreactive Nerve Fibers of the Anterior Pituitary to Adrenalectomy in the Rat

Abstract: The mammalian anterior pituitary is known to be regulated by humoral factors only, no direct neural influence having ever been discovered. Our recent studies have shown in several species that there are substantial amounts of substance P and calcitonin-gene-related peptide-like immunoreactive (CGRP-LI) nerve fibers in the anterior pituitary and that they can make synaptic contacts with secretory cells, among which corticotropes. In the present study, we investigated changes in CGRP-LI nerve fibers of the anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

1995
1995
1998
1998

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
(22 reference statements)
2
16
1
Order By: Relevance
“…The increase in GAP-43-LI is much more prominent than the increase in CGRP-like immunoreactivity demonstrated pre¬ viously. In the case of the CGRP-LI study (Ju et al 1994) there was a 1-7-fold increase in the average area density of the nerve fibers following adrenalectomy, -whereas in the present case the increase was 37-fold. But CGRP-LI nerve fibers are not the only kind of nerve fibers present in the anterior pituitary.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…The increase in GAP-43-LI is much more prominent than the increase in CGRP-like immunoreactivity demonstrated pre¬ viously. In the case of the CGRP-LI study (Ju et al 1994) there was a 1-7-fold increase in the average area density of the nerve fibers following adrenalectomy, -whereas in the present case the increase was 37-fold. But CGRP-LI nerve fibers are not the only kind of nerve fibers present in the anterior pituitary.…”
Section: Discussioncontrasting
confidence: 68%
“…(also known as B-50, F-l, pp.46 and neuromodulin) is a 24 kDa, nervous system-specific, membrane phospho¬ protein which has been implicated in axonal growth and synaptic remolding of the nervous system (Benowitz & Routtenberg 1987, Benowitz et al 1988, Skene 1989, Woolf eí al. 1990, Gispen et al 1991, Curtís et al 1992, Kruger et al 1993, Meberg et al 1993 (Ju et al 1994). The present study has demonstrated a very large increase in GAP-43-LI under the same conditions.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations